296 Frequency of intraoperative consultation for upper abdominal primary debulking surgery in advanced ovarian cancer. (18th September 2019) - Cowan, R; Tseng, J; Dearie, HF; Zhou, Q; Iasonos, A; Long Roche, K; Zivanovic, O; Gardner, G; Sonoda, Y; Chi, D
Abstract : Objectives: To gauge the learning curve of gynecologic oncologist (GOs) by measuring their need for intraoperative consultants in upper abdominal primary debulking surgery for advanced ovarian cancer (OC). Methods: Patients with bulky upper abdominal disease (UAB) undergoing primary debulking surgery (PDS) for OC from 1/2001–12/2013 were included. UAB was defined as tumor >1 cm cephalad to the omentum. Extensive procedures included diaphragm resection/peritonectomy, splenectomy, distal pancreatectomy, partial liver resection, resection of tumor from the porta hepatis, partial gastrectomy, and cholecystectomy. Results: Of 585 patients identified, 452 (77%) underwent UAS. The most common procedures were diaphragm resection (n=413), splenectomy (n=141), and liver resection (n=97). Over the 13-year period, the rate of patients undergoing UAS increased from 77% to 84% (p=0.019). Median number of UAS procedures was 1 (range, 1–7), remaining constant over time (p=0.129). The percentage of UAS procedures performed by consultants decreased over time, from 100% in the first quartile to 50% in the last (p<0.001). Procedures most commonly performed by consultants were cholecystectomy (89%), porta hepatis (76%) and liver resection (76%). The complete gross resection (CGR) rate increased from 18% to 46% (p<0.001). Median 3-year OS increased from 56% (95% CI, 45.9–65%) to 77% (95% CI 70.2–82%), p<0.001. OS was similar among patients who underwent UAS by a consultant versus a GO (p=0.308). Conclusions: GOs who attain the learning curve perform UAS with maximal cytoreduction, with a success rate similar to that of intraoperative consultants. Including UAS in the surgical armamentarium contributes to increased rates of CGR.